2021
DOI: 10.1002/jtr.2486
|View full text |Cite
|
Sign up to set email alerts
|

How do locals perceive the touristification of their food market? The case of Barcelona's La Boqueria

Abstract: Overtourism has become a major issue of concern in many popular venues, including several cities like Barcelona. In this study, in order to better comprehend reactions towards overtourism, we analyze the perceptions of residents who regularly shop at Barcelona's La Boqueria towards the growing crowds of tourists who visit the same venue. The study aims to acknowledge the evolution over time of locals' aversion or support regarding the touristification of their food market and to determine whether or not overto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Finally, it is worth noting that specific studies have not yet analysed the relationship between place identity and touristification. The closest studies highlight the relationship between place attachment and tourism development (Stylidis, 2018;Dimitrovski et al, 2022). Place identity has sometimes served to protect heritage resources or cultural manifestations of local communities (Liu & Cheng, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth noting that specific studies have not yet analysed the relationship between place identity and touristification. The closest studies highlight the relationship between place attachment and tourism development (Stylidis, 2018;Dimitrovski et al, 2022). Place identity has sometimes served to protect heritage resources or cultural manifestations of local communities (Liu & Cheng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tourist areas need specific and precise policies that, in addition to the traditional measures related to the control and regulation of tourist accommodation, the hospitality industry and the occupation of space (Wall & Mathieson, 2006;Mihalic, 2020;López et al, 2022;Dimitrovski et al, 2022), guarantee services and facilities that reinforce the value of the community in the neighbourhoods as spaces of real social reproduction (Cocola-Gant, 2023). In particular, it is necessary to rethink and plan specific actions, such as the massive pedestrianisation of the old town, which has favoured the expansion of the hospitality industry and absorbed significant investments to the detriment of the peripheries (Hernández Pezzi, 2018).…”
Section: Like Other Historic Centres Inmentioning
confidence: 99%
“…Secondly, there is a trend towards the touristification of public services, describing a situation in which public services, which are typically provided for the benefit of local residents, are heavily influenced or adapted to cater to the needs and preferences of tourists. This includes changes in local supply systems, traffic congestion, and the emergence of new venues [44]. Balancing the benefits and challenges of touristification of public services is essential because this phenomenon can have both positive and negative effects, depending on the context.…”
Section: Tourism Gentrification In Traditional Industrial Areasmentioning
confidence: 99%
“…Regarding the relationship between place attachment and attitude towards tourism development, literature presents different results. Some papers find that there is no significant direct relationship between place attachment and support for tourism development (Dimitrovski, Crespi-Vallbona and Ioannides, 2022;Ganji, Johnson and Sadeghian, 2020;Gannon et al, 2021;Gursoy, Jurowski and Uysal, 2002;Jurowski, Uysal and Williams, 1997;Nugroho andNumata, 2022, Stylidis, 2020), while others show a significant direct relationship. More specifically, most research finds a positive relationship, regardless of the type of tourism to support: heritage tourism (Chen and Chen, 2010), sustainable community tourism (Choi and Murray, 2010), sustainable tourism (Gursoy and Rutherford, 2004;Lee, 2013;Nicholas et al, 2009;Orgaz-Agüera et al, 2022), island tourism (Eusébio, Vieira and Lima, 2018), gaming tourism (Lee et al, 2020;Luo andXiao, 2017), ethnic tourism (Wang et al, 2020), film tourism (Castro, Kim and Assaker, 2023), festival tourism (Eluwole et al, 2022) or mass tourism (Hateftabar and Chapuis, 2020;Li, Pan and Hu, 2021;Shen, Geng and Su, 2019;Shen and Shen, 2021).…”
Section: 3) Residents' Place Attachment and Its Effect On The Attitud...mentioning
confidence: 99%
“…Most studies point out that the relationship depends on the type of impact, considering if it is a positive or negative impact, or if it is an economic, social or environmental impact. Some works (Choi and Murray, 2010;Eusébio et al, 2020;Nugroho and Numata, 2022) found that strongly attached residents perceived the positive impacts higher and the negative impact lower, but most studies state that attachment has a significant influence on benefits, but not on perceived costs (Chen and Chen, 2010;Chen and Raab, 2012;Dimitrovski et al, 2022;Luo and Xiao, 2017;Gursoy et al, 2019;Kendall, 2006, Lee, 2013). More specifically, Gursoy and Rutherford (2004) show that attachment influences the perceived economic and social benefits, but not the cultural benefits.…”
Section: 4) the Mediating Role Of Perceived Impacts Between Residents...mentioning
confidence: 99%